Elevation and Mass Changes of the Southern Patagonia Icefield Derived from TanDEM-X and SRTM Data - Malz, Philipp; Meier, Wolfgang; Casassa, Gino; Jana, Ricardo; Skvarca, Pedro; Braun, Matthias H. (My University, 2018)
The contribution to sea level rise from Patagonian icefields is one of the largest mass losses outside the large ice sheets of Antarctica and Greenland. However, only a few studies have provided large-scale assessments in a spatially detailed way to address the reaction of individual glaciers in Patagonia and hence to better understand and explain the underlying processes. In this work, we use repeat radar interferometric measurements of the German TerraSAR-X-Add-on for Digital Elevation Measurements (TanDEM-X) satellite constellation between 2011/12 and 2016 together with the digital elevation model from the Shuttle Radar Topography Mission (SRTM) in 2000 in order to derive surface elevation and mass changes of the Southern Patagonia Icefield (SPI). Our results reveal a mass loss rate of -11.84 +/- 3.3 Gta(-1) (corresponding to 0.033 +/- 0.009 mma(-1) sea level rise) for an area of 12573 km(2) in the period 2000-2015/16. This equals a specific glacier mass balance of -0.941 +/- 0.19 m w.e.a(-1) for the whole SPI. These values are comparable with previous estimates since the 1970s, but a magnitude larger than mass change rates reported since the Little Ice Age. The spatial pattern reveals that not all glaciers respond similarly to changes and that various factors need to be considered in order to explain the observed changes. Our multi-temporal coverage of the southern part of the SPI (south of 50.3 degrees S) shows that the mean elevation change rates do not vary significantly over time below the equilibrium line. However, we see indications for more positive mass balances due to possible precipitation increase in 2014 and 2015. We conclude that bi-static radar interferometry is a suitable tool to accurately measure glacier volume and mass changes in frequently cloudy regions. We recommend regular repeat TanDEM-X acquisitions to be scheduled for the maximum summer melt extent in order to minimize the effects of radar signal penetration and to increase product quality.
Keywords: glacier elevation change; geodectic mass balance; insar; patagonia; spi